2019
DOI: 10.3390/educsci9020143
|View full text |Cite
|
Sign up to set email alerts
|

Self-Acceptance in Black and White

Abstract: This reflective, autoethnographic qualitative case study at focus in this article is based on broader research on the experiences of Black teachers working at predominantly white and affluent private schools in the United States. It was motivated by the author/researcher’s own experiences of personal, academic, and professional racial identity development as a student, educator, parent, and educational administrator while living and working in predominantly white and affluent communities. The two main research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
4
0
4
Order By: Relevance
“…Scholarship shows that teachers bring their experiences and cultural understandings with them into the classroom. These experiences inform the lens through which they develop curriculum and their subsequent teaching practices (Gilpin, 2005; Hasberry, 2019; Sparks, 2018). Our first finding affirms this research on teachers’ cultural influences on practices and curriculum (Black et al, 2019; Pereira et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Scholarship shows that teachers bring their experiences and cultural understandings with them into the classroom. These experiences inform the lens through which they develop curriculum and their subsequent teaching practices (Gilpin, 2005; Hasberry, 2019; Sparks, 2018). Our first finding affirms this research on teachers’ cultural influences on practices and curriculum (Black et al, 2019; Pereira et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is little discussion and understanding around how to support educators of color as they enter the white majoritarian field of education (Montecinos, 2004;Sleeter, 2001). Research has shown that individuals' complex racial identities and lived experiences shape their professional identity (Al-Khatib & Lash, 2017;Gilpin, 2005;Hasberry, 2019;Kayi-Adyar, 2019;Sparks, 2018). However, minoritized educators experience conflicts in forming their professional identity.…”
Section: Understanding the Identity Development Of Minoritized Educatorsmentioning
confidence: 99%
“…Intersectionality. Intersectionality centers around the idea that a social phenomenon can be viewed through various perspectives, various identities or various classifications (Hasberry, 2019). For the context of this study the social phenomenon of focus is being Black in a predominantly white working environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…When thinking of the experience there are several factors or variables that have an influential part. Intersectionality aims to better understand what part these variables have played and how they have impacted the experience of the individual (Hasberry, 2019). This study will aim to better understand the various perspectives of the participants have been impacted or shaped by variables including race and gender.…”
Section: Theoretical Frameworkmentioning
confidence: 99%